Use Sensory Analysis to Optimize Corn Seed Storage Methods in a Triple Bagging and Biopesticide System (Leaves of Lippia multiflora Moldenke and Hyptis suaveolens Poit) in Côte D’ivoire - Félix, N’Dri Kouakou; Daouda, Sidibé; Marius, Biego Henri; Chatigre, Kouamé Olivier (European Journal of Applied Sciences, 2025)
The effectiveness of dried leaves of Lippia multiflora and Hyptis suaveolens on maize grains stored in a triple bagging system was tested. A three-factor central composite design (CCD) affecting the storage of maize grains was used to monitor changes in sensory quality, namely moldy aroma and rancid odor, during storage. The first CCD factor comprised six observation periods: 0, 1, 4.5, 9.5, 14.5, and 18 months. The second factor was the type of treatment, which consisted of 1 control batch with polypropylene bags (WB) and 9 experimental batches, including 1 in a triple bag without biopesticides (TBS0) and eight (8) additional batches containing ratios and/or combinations of biopesticides (TB1 to TB8). Finally, the third factor concerned the combination of two biopesticides, with the percentage (%) of Lippia multiflora as the reference. The results indicate that the ideal conditions for maintaining the sensory quality of maize grains during storage, based on the intensity of the rancid odor and moldy aroma, are achieved under the following conditions: Storage period: 18 months, Ratio of biopesticides to maize: 2.5%- Combination of biopesticides: 100% Lippia multiflora or 100% Hyptis suaveolens under the best-expected conditions, the experimental values were: rancid odor 4.10±0.25 and musty aroma 3.70±0.37.